Archive management schedule and their role in determining the documents’ life cycle: Management Schedule of judicial archive documents in Algeria - Abdelhadi Abdelali (International Journal of Social Communication, 2024)
The management schedule of archival documents is considered a result of the cooperation between the employee in service that produce documents and archivist in institution. The management schedule can also be completed after a request from an authority or through an individual initiative by the archivist in the institution, depending on all the publications, notes and particular instructions for exclusion and the preservation of archival documents for its formation and its achievement. Management schedule archival documents serves as mean follows the effect of documents and controlling the massive flow of information circulating within the organization. From the other side the judicial management schedule of archival documents is considered lawful and organizational document, its first basic aim is determining the period of preservation for each produced documents its final fate by permanent preservation or exclusion comparing to the applicable legal texts or comparing with daily transactions and dealings in case of the lack of legal texts.